Multifunctional full-visible-spectrum optoelectronics based on a van der Waals heterostructure. (December 2019) - Yang, Shih-Hsien; Lee, Ko-Chun; Tsai, Meng-Yu; Chang, Yuan-Ming; Lin, Che-Yi; Yang, Feng-Shou; Watanabe, Kenji; Taniguchi, Takashi; Lien, Chen-Hsin; Ho, Ching-Hwa; Li, Mengjiao; Lin, Yen-Fu; et al.
Abstract: Multifunctional devices are expected to allow development of low-cost, highly integrated, and energy-efficient electronics for the internet of things (IoT) era. Here, we demonstrate an all-two-dimensional ReSe2 /h-BN/graphene heterostructure (ReSe2 HS) consisting of a vertically coupled ReSe2 field-effect transistor and charge storage component, which possesses multifunctional characteristics for use in electronics and optoelectronics. As an electrically controlled non-volatile memory (NVM), the ReSe2 HS delivers high-performance multilevel data storage with a readout on/off current ratio exceeding 10 5 and excellent durability (>10 4 s) at an ultralow V ds of 50 mV, which benefits to the development of power saving devices. The ReSe2 HS design and high-photoresponsivity ReSe2 channel also achieve an energy efficient optical NVM with full-visible-spectrum distinction. Besides, the ReSe2 HS displays unique ambipolarity to operate as either an inverter or frequency doubler. We further propose a power-free ReSe2 HS optical memory matrix to simplify imaging systems. The ReSe2 HS shows promise for use in light-programmable information storage systems and neuromorphic computation with low power consumption. Graphical abstract: A vertical van der Waals heterostructure stacked by ReSe 2 /h-BN/Graphene layers (ReSe 2 HS), is demonstrated for multiple optoelectronic applications with low power consumption, including electrically controlled non-volatile memory (NVM) with continuous data storage states, light-mediated memory with full-visible spectrum range, light-programmable circuit with unique operations, and promising filter-free imaging systems with low consumption. Image 1 Highlights: An all-2D photoelectricl nonvolatile memory (NVM) device has been demonstrated based on ReSe2 heterostructure (ReSe2 HS). ReSe2 HS exhibits multilevel storage characteristic and excellent retention property. The ReSe2 HS can be achieved full-visible-spectrum light-programmable features in inverter and frequency doubler. The ReSe2 HS is proposed to build a power-saving imaging sensors for energy efficient digital camera systems.